Geo-strategic importance of Nepal - Baniya, Dharma Bahadur (Unity Journal, 2020)
The destiny of a country, to a great extent, depends upon its geo-strategic position in the world. Nepal’s unique geo-strategic position has contributed to expand its roles and enhance its strategic significance in the regional as well as the global affairs. Our neighbors are taking interest in Nepal mainly because of its connectivity potential, natural resources and their security concerns. By realizing our geo-strategic importance, immediate neighbors and some established powers are trying to expand their influences in various forms, over Nepal. With this background, this article forwards relevant recommendations to exploit maximum benefits by analyzing the importance of geostrategic position of Nepal.